2016
DOI: 10.1093/humrep/dew013
|View full text |Cite
|
Sign up to set email alerts
|

The proteolytic activity of pregnancy-associated plasma protein-A is potentially regulated by stanniocalcin-1 and -2 during human ovarian follicle development

Abstract: This work was supported by grants from the Novo Nordisk Foundation, and the Danish Council for Independent Research. No competing interests declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 58 publications
4
49
0
Order By: Relevance
“…STC2 is highly expressed in GCs to modulate the angiogenic or steroidogentic pathways or principal processes in ovarian function . STCs play an important role during folliculogenesis; however, the regulator of STCs in the ovary has not been reported. Our results showed that low‐dose melatonin could downregulate STC expression.…”
Section: Discussionmentioning
confidence: 99%
“…STC2 is highly expressed in GCs to modulate the angiogenic or steroidogentic pathways or principal processes in ovarian function . STCs play an important role during folliculogenesis; however, the regulator of STCs in the ovary has not been reported. Our results showed that low‐dose melatonin could downregulate STC expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have investigated the impacts of these proteins on reproductive system function. STC1 was found to act downstream of adenyl cyclases in suppressing progesterone biosynthesis in STC‐mediated PAPPA proteolytic inhibition within human FF (Jepsen et al., ). ADAMTS9 increased expression in human granulosa cells after hCG treatment (Rosewell et al., ), as well as in dominant follicle of rhesus macaques after ovulatory stimulus (Peluffo, Murphy, Baughman, Stouffer, & Hennebold, ).…”
Section: Discussionmentioning
confidence: 99%
“…On contrary, human STC2 transgenic mice were 45% smaller than wildtype littermates (54). STC2's negative regulation of postnatal growth was demonstrated by its ability to interact with pregnancy-associated plasma protein-A (PAPP-A), potentially inhibiting its proteolytic activity toward insulin-like growth factor binding protein 4 (IGFBP4) and causing reduction in insulin-like growth factor (IGF) signaling (55,56). Recent genome-wide association studies identified rare height increasing alleles of STC2 with compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP4 resulting in higher bioavailability of IGF (57).…”
Section: Role In Animal Developmentmentioning
confidence: 99%